The Chelating Ability of Plant Polyphenols Can Affect Iron Homeostasis and Gut Microbiota - Aurelia Scarano; Barbara Laddomada; Federica Blando; Stefania De Santis; Giulio Verna; Marcello Chieppa; Angelo Santino (MDPI AG, 2023)
In the past decades, many studies have widely examined the effects of dietary polyphenols on human health. Polyphenols are well known for their antioxidant properties and for their chelating abilities, by which they can be potentially employed in cases of pathological conditions, such as iron overload. In this review, we have highlighted the chelating abilities of polyphenols, which are due to their structural specific sites, and the differences for each class of polyphenols. We have also explored how the dietary polyphenols and their iron-binding abilities can be important in inflammatory/immunomodulatory responses, with a special focus on the involvement of macrophages and dendritic cells, and how they might contribute to reshape the gut microbiota into a healthy profile. This review also provides evidence that the axes "polyphenol-iron metabolism-inflammatory responses" and "polyphenol-iron availability-gut microbiota" have not been very well explored so far, and the need for further investigation to exploit such a potential to prevent or counteract pathological conditions.